Analisa Kekokohan Tanggapan Tegangan Sistem Eksitasi Generator Tipe Arus Searah Dengan Berbagai Pengendali - Heru Dibyo Laksono; Doohan Haliman; Aidil Danas; Wayu Diafridho A (Jurusan Teknik Elektro Universitas Andalas, 2015)
The voltage response robustness of generator excitation system is the ability of generator excitation system to muffle noise at high frequency, has rapid response to specific input and is able to eliminate disturbance during operation. In this journal is conducted a discussion about the voltage response robustness analysis of generator excitation system with various controllers. By using the criteria of the maximum peak value, phase margin and gain margin are analyzed the voltage response robustness of generator excitation. The criteria of maximum peak value is divided into two specifically the criteria of the sensitivity maximum peak value and the criteria of the complementary sensitivity maximum peak value. The type of controllers are designed include Proportional controller (P), Proportional Integral controller (PI), Proportional Differential controller (PD), Proportional Integral Differential controller (PID), Proportional Differential controller with First Order Filter In Part Differential (PDF) and Proportional Integral Differential controller with First Order Filter in Part Differential (PIDF). The results showed that the voltage response of generator excitation system with Proportional controller (P), Proportional Integral controller (PI), Proportional Differential controller (PD), Proportional Integral Differential controller (PID) Proportional Differential controller with First Order Filter In Part Differential (PDF) and Proportional Integral Differential controller with First Order Filter in Part Differential (PIDF) is robust to disturbance, able to reduce noise at high frequencies and having rapid response to specific input. This is evidenced by sensitivity peak value smaller than 2.0000 and complementary sensitivity peak value smaller than 1.2500, the minimum limit of gain margin greater than 6.0000 dB and the minimum limit of phase margin between 30.0000 degrees to 60.0000 degrees for each controller.Keyword: robustness, excitation system, sensitivity maximum peak, complementary sensitivity maximum peak, gain margin, phase margin Abstrak— Kekokohan tanggapan tegangan sistem eksitasi generator merupakan kemampuan dari sistem eksitasi generator untuk meredam derau pada frekuensi tinggi, mempuyai tanggapan yang cepat terhadap masukan tertentu dan mampu menghilangkan gangguan pada saat beroperasi. Pada jurnal ini dilakukan pembahasan tentang analisa kekokohan tanggapan tegangan sistem eksitasi generator dengan berbagai pengendali. Dengan menggunakan nilai kriteria puncak maksimum dan kriteria margin penguatan dan margin fasa dilakukan analisa kekokohan pada tanggapan tegangan sistem eksitasi generator. Kriteria nilai puncak maksimum ini terbagi atas 2 bahagian yaitu nilai kriteria puncak maksimum sensitivitas dan nilai kriteria puncak maksimum sensitivitas komplementer. Untuk jenis – jenis pengendali yang digunakan terdiri dari pengendali Proporsional (P), pengendali Proporsional Integral (PI), pengendali Proporsional Diferensial (PD), pengendali Proporsional Integral Diferensial (PID), pengendali Proporsional Diferensial dengan filter orde pertama pada bagian diferensial (PDF) dan pengendali Proporsional Integral Diferensial dengan filter orde pertama pada bagian diferensial (PIDF). Hasil yang diperoleh bahwa tanggapan tegangan sistem eksitasi generator dengan pengendali Proporsional (P), pengendali Proporsional Integral (PI), pengendali Proporsional Diferensial (PD), pengendali Proporsional Integral Diferensial (PID), pengendali Proporsional Diferensial dengan filter orde pertama pada bagian diferensial (PDF) dan pengendali Proporsional Integral Diferensial Dengan Filter Orde Pertama (PIDF) bersifat kokoh terhadap gangguan, mampu meredam derau pada frekuensi tinggi dan mempuyai tanggapan yang cepat terhadap masukan tertentu. Hal ini dibuktikan dengan nilai puncak sensitivitas yang kecil dari 2.0000 dan nilai puncak sensitivitas komplementer yang kecil dari 1.2500, batasan minimum dari margin penguatan besar dari 6.0000 dB dan batasan minimum dari margin fasa antara 30.0000 derjat s/d 60.0000 derjat untuk setiap pengendali.Kata kunci : kekokohan, sistem eksitasi, puncak maksimum sensitivitas, puncak maksimum sentivitas komplementer, margin penguatan, margin fasa.